디카페인 캡슐 커피의 이화학적 특성 및 항산화 활성 비교 - 양시라; 박신영; 김인용 (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2025)
본 연구에서는 시판 중인 다양한 디카페인 캡슐 커피의 이화학적 특성과 항산화 활성을 분석하여 샘플 간 품질 특성의 차이를 확인했다. 스위스 워터 추출법이 적용된 샘플에서 TDS 값이 낮게 나타났으며, 디카페인 공정에 따라 pH에도 영향을 미치는 것으로 나타났다. 총 폴리페놀 및 플라보노이드 함량은 유사한 경향을 보였다. DPPH 라디칼 소거능은 디카페인 커피와 유사한 수준의 항산화 활성을 보였으며, ABTS 라디칼 소거 활성은 일반 커피와 비슷한 패턴을 보였다. 카페인 함량은 0.09~0.18 mg/mL로 나타났으며, 일반 캡슐 커피보다 낮은 수준으로 디카페인 공정을 통해 효과적인 카페인 제거가 이루어졌음을 확인했다. 디카페인 캡슐 커피는 일반 에스프레소에 비해 아세트산, 시트르산, 옥살산 함량이 낮고 말산 함량은 높은 경향을 보였다. 디카페인 커피가 일반 커피와는 다른 유기산 조성을 가질 수 있으며 디카페인 공정 및 원료의 차이가 품질 특성에 영향을 미친다. 상관분석 결과, 플라보노이드와 총 폴리페놀 함량 간에는 강한 양의 상관관계가 있었으며, DPPH 소거 활성과 카페인 함량 간에는 음의 상관관계가 나타났다. 디카페인 캡슐 커피는 일반 커피에 비해 카페인 함량을 효과적으로 줄이는 장점이 있으나, 맛과 향을 결정하는 기호 성분이 일부 손실될 수 있다. 따라서 디카페인 캡슐 커피의 공정별 특성과 기호 성분 변화에 관한 추가 연구가 필요하다. In this study, 10 types of domestically and internationally available decaffeinated coffee capsules were compared and analyzed to evaluate the differences in the quality and activity of each product. The samples were extracted as 40 mL espressos using a capsule coffee machine under the same conditions, and the physicochemical properties, including color, total dissolved solids, and pH, were measured. Additionally, antioxidant activities were assessed by evaluating the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging abilities, and the total phenol and flavonoid contents were determined. The analysis revealed that the DPPH radical scavenging ability ranged from 49.88±0.62% to 60.62±1.50%, and the ABTS radical scavenging ability ranged from 63.54±1.97% to 89.48±1.12%, showing significant variation among the samples. Caffeine content varied from 0.09 mg/mL to 0.18 mg/mL, indicating considerable differences in product quality despite the same decaffeinated labeling. Moreover, a strong positive correlation between the flavonoid and total phenol content was observed (r=0.95), while a negative correlation was found between DPPH radical scavenging activity and pH (r=-0.87). These findings suggest that differences in the quality and activity of decaffeinated coffee capsules exist between products, which could significantly influence consumer choice. KCI Citation Count: 0